2020
DOI: 10.1007/s12031-020-01700-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-and Region-Dependent Expression of the Autism-Linked ADNP Correlates with Social- and Speech-Related Genes in the Canary Brain

Abstract: The activity-dependent neuroprotective protein (ADNP) syndrome is an autistic-like disorder, instigated by mutations in ADNP. This syndrome is characterized by developmental delays, impairments in speech, motor function, abnormal hearing, and intellectual disabilities. In the Adnp-haploinsufficient mouse model, many of these impediments are evident, appearing in a sex-dependent manner. In zebra finch songbird (ZF; Taeniopygia guttata), an animal model used for song/language studies, ADNP mRNA most robust expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Our previously published studies have suggested that ADNP/NAP regulate FOXP2 in the tongue [ 51 ] and that NAP regulates FOXP2 in the brain [ 69 ]. Furthermore, we showed that the expression of ADNP is highly correlated with FOXP2 expression in the brain [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previously published studies have suggested that ADNP/NAP regulate FOXP2 in the tongue [ 51 ] and that NAP regulates FOXP2 in the brain [ 69 ]. Furthermore, we showed that the expression of ADNP is highly correlated with FOXP2 expression in the brain [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no animal model can fully capture the behavior and genetic complexity of ASD, as an experimental language learning animal model, songbirds can supplement the shortcomings of rodent genetic models and provide essential insights into communication deficiencies. For instance, zebra finches communicate through learned vocalizations and can be used to simulate language communication disorders ( Ahmadiantehrani & London, 2017 ; Hacohen-Kleiman et al, 2020 ; Panaitof, 2012 ). Moreover, recent genomic research has identified potential genetic substrates for the evolution and regulation of vocal communication ( Warren et al, 2010 ).…”
Section: Common Animals Used In Asd Studymentioning
confidence: 99%
“…The sex- and age-related expression of ADNP mRNA was reported in different areas (cerebellum, cerebrum, brainstem) of the zebra finch ( Hacohen-Kleiman et al, 2015 ), with a distinct sexual dimorphism (young males expressing higher levels of ADNP than females, in agreement with the notion that only males perform courtship singing). The gene expression profile was largely confirmed in the domesticated canary, and ADNP mRNA was found to be enriched mainly in the mesopallium, harboring centers for sensory integration and higher auditory processing ( Hacohen-Kleiman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%